Próba określenia wpływu obciążenia osiowego na wybrane cechy postawy ciała szermierzy = An attempt to determine the effect of the axial load on selected posture fencers - Mrozkowiak, Mirosław; Sokołowski, Marek; Kaiser, Alicja (Journal of Education, Health and Sport, 2016)
Mrozkowiak Mirosław, Sokołowski Marek, Kaiser Alicja. Próba określenia wpływu obciążenia osiowego na wybrane cechy postawy ciała szermierzy = An attempt to determine the effect of the axial load on selected posture fencers. Journal of Education, Health and Sport. 2016;6(10):309-320. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.162556 http://ojs.ukw.edu.pl/index.php/johs/article/view/3949 https://pbn.nauka.gov.pl/sedno-webapp/works/753681 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.10.2016. Revised 02.10.2016. Accepted: 20.10.2016. Próba określenia wpływu obciążenia osiowego na wybrane cechy postawy ciała szermierzy An attempt to determine the effect of the axial load on selected posture fencers Mirosław Mrozkowiak1, Marek Sokołowski2, Alicja Kaiser3 1 Firma „AKTON”, Szczecinek, Poland 2 Department of Modern and Defensive Sports, University School of Physical Education in Poznań, Poland 3 Department of Tourism and Recreation, WSB University in Poznań, Poland Streszczenie Cel. W prezentowanym doniesieniu podjęto problem oceny wpływu obciążenia wertykalnego na wybrane cechy przestrzennie opisujące kręgosłup, tułów i miednicę. Metoda. Badania przeprowadzono wśród 23 zawodniczek i zawodników szermierki w wieku od 12 do 19 lat. Metoda obejmowała pomiar 29 parametrów opisujących miednicę oraz fizjologiczne krzywizny kręgosłupa w postawie habitualnej i w obciążeniu wertykalnym 1/3 masy ciała badanego. Do oceny wartości wybranych parametrów, opisujących zespół miednicy-kręgosłupa wykorzystano stanowisko do komputerowej oceny postawy ciała. Wyniki: Zastosowane obciążenie standardowe wśród chłopców wywołało istotne zmiany w następujących cechach kręgosłupa: zmniejszyło długości i wysokości lordozy lędźwiowej, pogłębiło kąt i głębokość kifozy piersiowej, wyprost tułowia w płaszczyźnie strzałkowej, kąt nachylenia odcinka piersiowego górnego kręgosłupa i asymetrię barków w płaszczyźnie czołowej. Wśród dziewcząt istotne i pogłębiające wielkości cech zaobserwowano w: kącie i głębokości kifozy piersiowej, sumie kątów cząstkowych delta, kącie nachylenia odcinka piersiowo-lędźwiowego kręgosłupa oraz kącie kilkustopniowej lewostronnej skoliozy. Wnioski: 1. Zastosowane obciążenie wśród chłopców najistotniej wpłynęło na cechy strzałkowe kręgosłupa, mniej czołowe, nie wpłynęło na cechy w płaszczyźnie poprzecznych. Przy czym najistotniej na długość i wysokość lordozy lędźwiowej i głębokość kifozy piersiowej, co nie korygowane może prowadzić do zmian przeciążeniowych w odcinku L-S kręgosłupa. Wśród dziewcząt najistotniej na głębokość kifozy piersiowej i sumę kątów cząstkowych (Delta). 2. W treningu uzupełniającym szkolenie zasadnicze szermierzy należy w większym stopniu uwzględnić siłę mięśni posturalnych. Wśród szermierek z większym akcentem na obszar kifozy piersiowej i deficyty zakresów ruchu stawów biodrowych i barkowych. Słowa kluczowe: posturę, spine, pelvis, kyphosis, szermierka Summary Objective. In report presented with the problem of assessing the impact of the vertical load on selected spatially describing the spine, thorax and pelvis. Method. The study was conducted among 23 athletes fencing in age from 12 to 19 years. The method consisted of measuring 29 parameters describing the pelvis and the physiological curvature of the spine in the attitude of habitual and a vertical load of 1/3 of the weight of the subject. To assess the value of selected parameters that describe a team-pelvic spine position used for computer evaluation of body posture. Results: The applied load standard among boys resulted in significant changes in the spine following characteristics: reduced length and height of lumbar lordosis, deepened the angle and depth of thoracic kyphosis, straighten the body in the sagittal plane, the angle of inclination of the upper thoracic spine and shoulder asymmetry in the frontal plane. Among girls relevant and deepening the size of the features observed in angle and depth of thoracic kyphosis, the sum of the angles of partial delta angle of the thoraco-lumbar spine and the corner in several steps in the left hand side of scoliosis. Conclusions: 1. Applied load among boys most kind of major influenced the characteristics of spinal sagittal, frontal less, it did not affect the characteristics of the transverse plane. Most kind of major wherein the length and height of the lumbar lordosis and thoracic kyphosis depth, which is not corrected can lead to changes in the distance L overload S-spine. Among girls most kind of major depth of thoracic kyphosis and partial sum of the angles (Delta). 2. In practice supplementary training essential fencers should be taken more into account the strength of postural muscles. Among the fences with a greater emphasis on the area of thoracic kyphosis and deficits ranges of motion of the hip joints and shoulder. Key words: posture, spine, pelvis, kyphosis, fencing